Profitability efficiency, marketability efficiency and technology gaps in Taiwan's banking industry: meta-frontier network data envelopment analysis. Issue 3 (14th January 2018) - Chao, Chuang-Min; Yu, Ming-Miin; Hsiung, Nan-Hsing; Chen, Li-Hsueh
ABSTRACT: The aim of this article is to measure the profitability efficiency (PE) and marketability efficiency (ME) of non-homogenous Taiwanese banks after the adoption of International Financial Reporting Standards by using the convex meta-frontier data envelopment analysis model. The model is applied to simultaneously estimate PE and ME of the banks in financial holding companies (FHCs) and the banks not in FHCs. The meta-inefficiencies in individual processes are further decomposed into group inefficiencies and technology gap inefficiencies to explore the sources of inefficiency. The empirical results indicate that the banks in FHCs can reduce more costs than the banks not in FHCs, whereas the banks not in FHCs can create greater market value than the banks in FHCs. For the banks joining and not in FHCs, technology gap inefficiency is the main source of inefficiencies in both profitability and marketability processes.